Pengaruh Kepemilikan Asing terhadap Kinerja Perusahaan Manufaktur di Indonesia - Priyanto, Eko Adi; Qibthiyyah, Riatu Mariatul (Jurnal Kebijakan Ekonomi, 2019)
This study analyzes the influence of the level of company ownership and also analyzes further about evaluating the requirements of foreign capital ownership as a Negative Investment List (NIL). This study uses a panel of Indonesian manufacturing companies 2007-2014 with the estimated GMM method of Arellano-Bond. The estimation results show an increase achieved with foreign ownership, but after reaching a certain point the increase or increase as intended inverted U. Required to achieve optimal needs. Then further analysis showed that NIL Regulations were approved by foreign capital ownership, NIL companies' foreign capital ownership was lower than Non-NIL companies, but the increase in NIL companies on average was lower.